Pore structure description of mortars containing ground granulated blast-furnace slag by mercury intrusion porosimetry and dynamic vapour sorption - Alderete, Natalia Mariel (2017)
The description of the pore structure is a key aspect when studying the durability of cement-based materials. Many techniques have been developed over the years in order to describe the actual complex microstructure of these materials. These techniques can be useful to determine the change in pore structure when supplementary cementitious materials are used and also track its evolution with time. This paper particularly aims to describe the changes in the pore structure of mortars with contents of 20, 40 and 60% of ground-granulated blast-furnace slag (GGBFS) in replacement of cement, at the ages of 28 and 90 days. Two widely accepted techniques were applied: dynamic water vapour sorption (DVS) and mercury intrusion porosimetry (MIP). For the data analysis from the DVS test, the Barret-Joyner-Halenda (BJH) model was used for pore size distribution assessment. Moreover, since the extent of this model does not cover the smallest range of pores, calculations with the Dubinin-Radushkevich (DR) model were also made. Results from the MIP test were used to characterize the threshold diameter, the smallest intrudable diameter, and the intrudable porosity. GGBFS replacement leads to a slight increase in porosity values at 28 days, especially seen in the DVS results for the pore size range of 0.002–0.05 µm. DVS results at 90 days for the mix with 40% slag replacement showed a marked reduction in porosity and a shift in pore structure to the finer pore size range when compared to the 28 day results. For all cases, the total porosity was found to be less influential on the test results than pore connectivity.